Right Of Merit In Civil Evidence - Comparative Study - Mhmood Alfaidhi, Awan Abdullah (Opción, 2019)
It goes without saying that the Right of Merit is a special right that is of great importance as it is a remedy that limits the disadvantages of the system of re- stricting the evidence, which can not be dispensed with for justice and stability of transactions, it is necessary that this right to give an opportunity to those who were safe from the Kid’s opponent, The person who claims the right to a certain property, such as claiming ownership of things that are reserved, for example, must first prove ownership of the money. If the plaintiff proves his entitlement to these reserved objects, he should The Court’s amendment of the Meeting itself and with- out the need to request from his opponent to the right of the Astthbat he did not sell this money and did not give him to one and did not get it out of his property in any way possible faces. The right does not arrive at the court unless it is fully proven to the full benefit of the money by means of legal evidence. This right is obligatory because it obligates the court to direct it despite the complete evidence before it, because the plaintiff has in fact proved his case and the court has no dis- cretion in directing it or not. It is necessary to direct it on its own because the law is this evidence is incomplete in the case originally, and must be strengthened by a complementary right is right of merit that the plaintiff did not sell this money and did not give it to anyone and did not get out of his property.